Tuning the optimal diffusion-weighted MRI parameters on a 0.35-T MR-Linac for clinical implementation: A phantom study - Nardini, Matteo; Capotosti, Amedeo; Mazzoni, Lorenzo Nicola; Cusumano, Davide; Boldrini, Luca; Chiloiro, Giuditta; Romano, Angela; Valentini, Vincenzo; Indovina, Luca; Placidi, Lorenzo (Frontiers in Oncology, 2022)
Purpose The aim of this study is to assess the quality of a new DWI sequence implemented on a MR-Linac MRIdian system, evaluating and optimizing the acquisition parameters to explore the possibility of clinically implementing a DWI acquisition protocol in a 0.35T MR-Linac. Materials and methods. All the performed analyses have been carried out on two types of phantoms: a homogeneous 24 cm diameter polymethylmethacrylate (PMMA) sphere (SP) and a homemade phantom (HMP) constating in a PMMA cylinder filled with distilled water with empty sockets into which 5 cylindrical vials filled with five different concentrations of methylcellulose water solutions. SP was used to evaluate the dependence of diffusion gradient inhomogeneity artefacts on gantry position. Four diffusion sequences with b-values of 500 s/mm2 and 3 averages have been acquired: three with diffusion gradients in the three main directions (phase direction, read direction, slice direction) and one with the diffusion gradients switched off. The dependence of diffusion image uniformity and SNR on the number of averages in the MR sequences was also investigated to determine the optimal number of averages. Finally, ADC values of HMP have been computed and then compared between images acquired in the scanners at 0.35T and 1.5 T. Results In order to acquire high quality artefact-free DWI images, the “slice” gradient direction has been identified to be the optimal one and 0° the best gradient angle. Both the SNR ratio and the uniformity increase with the number of averages. A threshold value of 80 for SNR and 85% for uniformity was adopted to choose the best number of averages. By making a compromise between time and quality and limiting the number of b-values, it is possible to reduce the acquisition time to 78 seconds. Passing-Bablok test showed that the two methods, with 0.35 T and 1.5T scanners, led to similar results. Conclusion The quality of the DWI has been accurately evaluated in relation to different sequence parameters and optimal parameters have been identified to select a clinical protocol for the acquisition of ADC maps sustainable in the workflow of a hybrid radiotherapy system with 0.35 T MRI scanner.